2012
DOI: 10.1091/mbc.e12-05-0358
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for cooperation of Mia40 and Erv1 in the oxidation of mitochondrial proteins

Abstract: The mechanisms that underlie the oxidative biogenesis of mitochondrial proteins catalyzed by disulfide carrier Mia40 and thiol oxidase Erv1 are not fully understood. This study identifies dynamics of the Mia40–substrate intermediate complex and shows that Erv1 directly participates in Mia40–substrate dynamics by forming a ternary complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 41 publications
(81 reference statements)
2
54
0
3
Order By: Relevance
“…This process is facilitated by two essential components of the MIA pathway, Mia40 and Erv1 and leads to trapping of IMS precursors within the organelle due to oxidative folding (47)(48)(49). Mechanistic studies have demonstrated that the MIA pathway relies on the coordinated action of its two central players, Mia40 and Erv1, and also on the reducing power of glutathione, to execute disulfide transfer reactions efficiently by minimizing unproductive intermediate stages (50)(51)(52). These features ensure that the MIA system works efficiently despite the fact that the IMS is continuous with the reducing environment of the cytosol (53).…”
Section: Figmentioning
confidence: 99%
“…This process is facilitated by two essential components of the MIA pathway, Mia40 and Erv1 and leads to trapping of IMS precursors within the organelle due to oxidative folding (47)(48)(49). Mechanistic studies have demonstrated that the MIA pathway relies on the coordinated action of its two central players, Mia40 and Erv1, and also on the reducing power of glutathione, to execute disulfide transfer reactions efficiently by minimizing unproductive intermediate stages (50)(51)(52). These features ensure that the MIA system works efficiently despite the fact that the IMS is continuous with the reducing environment of the cytosol (53).…”
Section: Figmentioning
confidence: 99%
“…Upon protein synthesis in the cytosol, the cysteine residues of IMS proteins remain in a reduced state, owing to the reducing properties of the cytosolic environment (11,12). After entering the TOM channel, precursor proteins are specifically recognized by Mia40 protein, and their cysteine residues are oxidized through the cooperative action of Mia40 and Erv1 proteins (7,(13)(14)(15)(16)(17). Mia40 is a receptor, folding catalyst, and disulfide carrier, and the Erv1 protein serves as a sulfhydryl oxidase.…”
mentioning
confidence: 99%
“…In a previous study, we showed that Mia40 had a single midpoint potential of Ϫ290 mV, and at different redox potentials, one disulfide bond was reduced (19). However, recent studies suggested that Mia40 exists in intermediate oxidation states in mitochondria (28,29). Based on earlier publications in the literature that supported that only the CPC motif of Mia40 was redox active and could be reduced, we may have misinterpreted Mia40 oxidation in the presence of excess Tim13 in our previous study such that more than two cysteines of Mia40 were reduced by excess Tim13 (19).…”
Section: Resultsmentioning
confidence: 89%
“…Excess Mia40 can oxidize substrates in vitro (18,19,26), and recent studies in vivo support that Mia40 is present in a partially reduced state (28,29). Whereas these studies show that Mia40 is reduced, the specific redox state of Mia40 has not been determined.…”
mentioning
confidence: 93%